Determining the stem volume of a tree - M Muhdin (Institut Pertanian Bogor (IPB University), 2003)
Determining the stem volume of a tree has long been a problem for foresters, whereas, the need for an accurate estimate of wood volume is becoming more important. six volume equations were used and compared, for both constructing and validating models using data collected from Gmelina arborea Roxb. in the area P.T. Wanaksita Nusantara, Province of Jambi, Indonesia. The best equation obtained from model construction (fitting) step for a data may not necessarily be the best performance (shown from bias, precision and accuracy) for another data set though collected from the same population. For testing the occuracy of model, model validation is an important step in model construction process in order to get the best tree volume equation.